Acrylate-based pressure sensitive adhesives comprising hydrophobic oils
By adding hydrophobic oil to the acrylate copolymer and performing electron beam crosslinking, the problem of difficulty in maintaining adhesion and removal of adhesives on the skin for a long time is solved, and high oil loads and low oils suitable for medical applications are prepared The pressure-sensitive adhesive at the glass transition temperature achieves uniform adhesion and easy removal on the skin and stainless steel surfaces.
Patent Information
- Application Number
- CN202380039343.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-26
- Filing Date
- 2023-05-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing adhesives are difficult to maintain adhesion on the skin for a long time without raising, and tend to leave residues when removed, especially in medical applications, where the lack of sufficient cohesion strength and conformability leads to the adhesive Not suitable for long-term use and easy removal.
Pressure-sensitive adhesives with high corrected gel content and low glass transition temperature were prepared by adding 10% to 50% by weight of hydrophobic oil to the acrylate copolymer and using electron beam radiation crosslinking technology. , provides softer stickiness and controlled adhesion, suitable for smooth, rough and skin surfaces.
Adhesives that are uniformly adhered and easy to remove on the skin and stainless steel surfaces reduce adhesion accumulation, provide high oil loads and oil-free residue properties suitable for medical and other applications.
Smart Images

Figure BDA0005125228940000081 
Figure BDA0005125228940000091 
Figure BDA0005125228940000092
Abstract
Description
Technical Field
[0001] The present disclosure relates generally to the field of adhesives, and more particularly to the field of radiation cross-linked pressure sensitive adhesives containing acrylate copolymers and hydrophobic oils. Background Art
[0002] Adhesives are used for a variety of marking, fixing, protecting, sealing and masking applications. Adhesive tapes generally include a backing or substrate and an adhesive. One type of adhesive, pressure-sensitive adhesives, is particularly preferred for many applications. Pressure-sensitive adhesives ("PSAs") are well known to those of ordinary skill in the art and have certain properties at room temperature, including: (1) strong and permanent tack, (2) adhesion without exceeding finger pressure, (3) the ability to remain on an adherend, and (4) sufficient cohesive strength.
[0003] Materials that have been found to function well as pressure sensitive adhesives are polymers designed and formulated to exhibit the necessary viscoelastic properties resulting in a desired balance of tack, peel adhesion, and shear strength. Summary of the invention
[0004] In one aspect, the present disclosure provides a radiation-crosslinkable pressure-sensitive adhesive precursor comprising 50 wt % to 90 wt % of an acrylate copolymer comprising C4 to C16 acrylic acid monomers and 10 wt % to 50 wt % of a hydrophobic oil. The pressure-sensitive adhesive precursor mixture can be crosslinked using electron beam radiation to provide an adhesive composition having a corrected gel content greater than 50%, cleanly removable from stainless steel, and instantly wets smooth and structured surfaces, with controlled adhesion and low adhesion build-up.
[0005] In another aspect, methods of preparing such radiation-crosslinkable pressure-sensitive adhesive precursors and adhesives comprising the radiation-crosslinkable pressure-sensitive adhesive precursors in crosslinked form are provided.
[0006] In another aspect, provided herein are articles comprising these adhesives. DETAILED DESCRIPTION
[0007] In the present disclosure, singular forms such as “a”, “an” and “the” are often used for convenience. However, it should be understood that the singular forms are intended to include the plural meaning unless explicitly or by context solely referred to as the singular.
[0008] The most commonly used polymers for making pressure sensitive adhesives (PSAs) include natural rubber, synthetic rubbers (e.g., styrene / butadiene copolymers ("SBR") and styrene / isoprene / styrene ("SIS") block copolymers), various (meth)acrylate (e.g., acrylate and methacrylate) copolymers, and silicones.
[0009] A clean, easily removable (e.g., gentle to the skin) acrylate-based PSA is needed that has at least the benefits of a silicone gel-based PSA. Silicone gels are softer than silicone PSAs and have features such as, for example, resistance to lift, low residue, skin adhesion from "gentle" to "strong" that can be achieved by changing the formula, low temperature adhesion performance, masking and rough surface tape applications, and adhesion to oily surfaces. Similarly, acrylic PSAs tend to form strong bonds with skin and smooth surfaces such as stainless steel. Acrylic PSAs are used for medical skin-applied tapes, but a balance of cohesive strength, removal without peeling the skin, and sufficient compliance is required to maintain adhesion to the skin for more than 24 hours without edge lift. Acrylic PSAs are generally not modified with high levels of hydrophobic oils due to their inherent immiscibility and lack of cohesive strength.
[0010] The addition of hydrophobic oils combined with electron beam cross-linking provides softer gels, reduces long-term adhesion buildup, and facilitates the need for lower removal forces compared to traditional acrylates.
[0011] Adhesive composition and properties also depend on the intended use of the adhesive. Some uses require a gentle tape, while other uses require a forceful tape. If the adhesive is being adhered to a sensitive area of the body, a "gentle" tape is generally used. However, if it is important that the adhesive remain adhered for a long time, or if the adhesive is being adhered to an area that moves very easily, a more forceful tape is used. The term "gentle" adhesive generally refers to an adhesive whose adhesion does not substantially build up over time. The term "forceful" adhesive refers to an adhesive that has significant resistance to lifting or peeling.
[0012] Medical adhesives are commonly used in wound dressings, surgical drapes, bandages, and tapes. These items are typically made of a backing coated with an adhesive. A liner may or may not be used to protect the adhesive. The performance of the adhesive depends in part on the occlusive properties of the backing. Backings are typically classified as non-occlusive or occlusive based on their porosity. When non-occlusive backings are used to prepare bandages and the like for medical applications, the resulting bandages typically do not adhere well to the skin for extended periods of time. While not wishing to be bound by a particular theory, this may occur because the bandage is unable to release water vapor, which results in moisture retention and, in turn, causes the adhesive to lift from the skin.
[0013] Conformability and cohesion are two inversely related properties that are important considerations when preparing or selecting adhesives for medical applications. It is generally desirable that medical adhesives conform to the topography of the skin to which they are adhered, as this can enhance the comfort of the wearer and can also ensure a high initial adhesion to the skin, as the adhesive can flow into the topography of the skin. However, if the adhesive is too conformable, it may lack the cohesion necessary to remove the dressing from the skin with the adhesive intact. If the adhesive lacks cohesive strength, the adhesive on the bandage may split when attempting to remove the bandage, leaving some adhesive residue adhered to the skin, while some adhesive will be removed along with the bandage backing; this feature is unacceptable to most medical professionals and patients.
[0014] To address at least the issues discussed above, the present disclosure provides a hydrophobic oil gel acrylate pressure-sensitive adhesive ("PSA") that is softer than typical acrylic PSAs by adding a hydrophobic oil. The addition of a hydrophobic oil produces an adhesive that can be used to bond to smooth surfaces, rough surfaces, and skin surfaces. These PSAs can have features such as, for example, high oil loading (i.e., 10 wt % to 50 wt %), high corrected gel content (i.e., greater than 50 wt %), no oily residue, and a low glass transition temperature ("T g ”) and resulting in immediate wetting, where -60°C <T g <-20℃.
[0015] In some embodiments, a radiation-crosslinkable pressure-sensitive adhesive precursor is provided, which contains 40 wt % to 90 wt %, optionally 40 wt % to 80 wt %, optionally 50 wt % to 90 wt %, optionally 50 wt % to 80 wt % of an acrylate copolymer and 10 wt % to 50 wt %, optionally 20 wt % to 40 wt % of a hydrophobic oil.
[0016] Acrylate copolymer
[0017] Acrylate copolymers useful in embodiments of the present disclosure are known in the art and are described, for example, in U.S. Pat. No. 9,102,774 (Clapper et al.), U.S. Reissue Patent 24,906 (Ulrich), and U.S. Pat. No. 5,804,610 (Hamer et al.). Such acrylate copolymers can be prepared from C4 to C16 acrylic acid monomers by methods known to those of ordinary skill in the relevant art.
[0018] In some preferred embodiments, C4 to C16 acrylic acid monomers include 10 wt % to 100 wt %, optionally 20 wt % to 80 wt %, optionally 30 wt % to 70 wt % of C10 to C16 acrylic acid monomers. The C10 to C16 acrylic acid monomers that can be used in the embodiments of the present disclosure include a group consisting of primary ("1°") acrylic acid monomers, secondary ("2°") acrylic acid monomers, and combinations thereof. Examples of such C10 to C16 acrylic acid monomers may include, but are not limited to, decyl acrylate, isononyl acrylate, dodecyl acrylate, 2-propylheptyl acrylate, isodecyl acrylate, tridecyl acrylate, 2-decyl acrylate, 2-dodecyl acrylate, 2-tetradecyl acrylate, and combinations thereof.
[0019] In some preferred embodiments, C4 to C16 acrylic acid monomers include 10 wt % to 100 wt %, optional 20 wt % to 80 wt %, optional 30 wt % to 50 wt % C4 to C8 acrylic acid monomers. The example of such C4 to C8 acrylic acid monomers may include but is not limited to butyl acrylate, hexyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, 2-octyl acrylate, isooctyl acrylate and their combination. In some preferred embodiments, the radiation crosslinkable pressure-sensitive adhesive precursor of the present disclosure includes an acrylate copolymer that does not contain insoluble gel, as measured by testing through correction gel. In some preferred embodiments, the radiation crosslinkable pressure-sensitive adhesive precursor of the present disclosure includes an acrylate copolymer that does not contain multifunctional acrylate (such as, for example, hexanediol diacrylate, trimethylolpropane triacrylate). In some preferred embodiments, the radiation crosslinkable pressure sensitive adhesive precursor can have a weight average molecular weight ("Mw") of 500,000 to 1,500,000 g / mol, optionally 750,000 to 1,000,000 g / mol as determined by gel permeation chromatography ("GPC").
[0020] Hydrophobic Oil
[0021] Hydrophobic oils that can be used in embodiments of the present disclosure are typically oils with low solubility (i.e., <1% by weight) in water. Examples of such commercially available hydrophobic oils include paraffinic oils, such as KAYDOL USP grade oils available from Sonneborn, Inc. and CALSOL 9 series available from Calumet Specialty Products Partners, LP, Indianapolis, Indiana.; naphthenic oils, such as CALSOL 5 series with a molecular weight in the range of 350gr / mol to 1000gr / mol, available from Calumet Specialty Products Partners, LP, Indianapolis, Indiana; and polypropylene glycols with a molecular weight in the range of 400gr / mol to 2000gr / mol, such as polyethanol P-1000E and P-2000E from Dow Chemical Company, Midland, Michigan.
[0022] Another class of potentially useful hydrophobic oils are polybutenes with terminal unsaturation, such as, for example, the INDOPOL L and H series from Ineos Oligomers, League City, Texas, and hydrogenated polybutenes, such as, for example, the PANALANE L and H series from Vantage Specialty Chemicals, Deerfield, Illinois. Useful polybutenes typically have a molecular weight in the range of 350 gr / mol to 1500 gr / mol.
[0023] It has been observed that the presence of aromatic content may reduce the efficiency of electron beam curing.Hydrophobic oils compatible with embodiments of the present disclosure minimally interfere with the electron beam curing step.
[0024] Additional additives
[0025] The radiation-crosslinkable pressure-sensitive adhesive precursors of the present disclosure may include additional additives, depending on the desired properties of the resulting crosslinked pressure-sensitive adhesive.
[0026] In some embodiments, the radiation crosslinkable pressure-sensitive adhesive precursor may further include up to 5 wt%, optionally up to 4 wt%, or optionally up to 2 wt% of a polar acrylic monomer. Examples of polar acrylic monomers that can be used in embodiments of the present disclosure include, but are not limited to, acrylic acid, N,N-dimethylacrylamide, and combinations thereof.
[0027] In some embodiments, the radiation crosslinkable pressure sensitive adhesive precursor may further comprise up to 10 wt %, up to 5 wt %, up to 4 wt %, or up to 2 wt % of a high T g Acrylate monomers. High T g Examples of acrylate monomers include, but are not limited to, isobornyl acrylate, polystyrene macromonomers, and combinations thereof.
[0028] In some embodiments, the radiation-crosslinkable pressure-sensitive adhesive precursor may include an additive selected from the group consisting of a photoinitiator, a chain transfer agent, an antioxidant, a tackifying resin, and combinations thereof.
[0029] In some embodiments, the radiation-crosslinkable pressure-sensitive adhesive precursor may include a certain amount of photoinitiator, measured in parts per hundred parts of acrylic acid monomer ("pphm"). In some preferred embodiments, the radiation-crosslinkable pressure-sensitive adhesive precursor may include up to 0.1 pphm, up to 0.5 pphm, or up to 1 pphm of photoinitiator. Examples of photoinitiators that can be used in the embodiments of the present disclosure include, but are not limited to, 2,2-dimethoxy-1,2-diphenylethan-1-one (commercially available as OMNIRAD 651 (formerly known as IRGACURE 651) from IGM Resins USA Inc., Charlotte, North Carolina), 2-hydroxy-2-methyl-1-phenyl-propan-1-one (commercially available as OMNIRAD 1173) from IGM Resins USA Inc., 1-hydroxy-cyclohexyl-phenyl ketone (OMNIRAD 184) from IGM Resins USA Inc., and combinations thereof.
[0030] In some embodiments, the radiation cross-linkable pressure-sensitive adhesive precursor may include a certain amount of chain transfer agent, in parts per hundred parts of acrylic acid monomer ("pphm"). In some preferred embodiments, the radiation cross-linkable pressure-sensitive adhesive precursor may include a chain transfer agent of at most 0.001 pphm, at most 0.005 pphm, or at most 0.01 pphm. Examples of chain transfer agents that can be used in embodiments of the present disclosure include, but are not limited to, isooctyl thioglycolate ("IOTG"), carbon tetrabromide ("CBr4"), and combinations thereof.
[0031] In some embodiments, the radiation-crosslinkable pressure-sensitive adhesive precursor may include a certain amount of antioxidant, measured in parts per hundred parts of acrylic acid monomer ("pphm"). In some preferred embodiments, the radiation-crosslinkable pressure-sensitive adhesive precursor may include up to 0.1 pphm, up to 0.2 pphm, up to 0.5 pphm, or up to 1 pphm of antioxidant. Examples of chain antioxidants that can be used in the embodiments of the present disclosure include, but are not limited to, primary antioxidants, such as hindered phenols, including IRGANOX 1076 (octadecyl-[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and IRGANOX 1010 (pentaerythritol tetrakis[3-[3,5-di-tert-butyl-4-hydroxyphenyl] propionate) antioxidants, both of which are available from BASF Corporation, and combinations thereof.
[0032] In some embodiments, the radiation crosslinkable pressure-sensitive adhesive precursor may further comprise up to 20 wt%, up to 10 wt%, up to 5 wt%, or up to 1 wt% of a tackifying resin. The solid tackifying resin useful in embodiments of the present disclosure generally produces tack in the adhesive comprising the radiation crosslinkable pressure-sensitive adhesive precursor and has a softening point ("SP") below 120°C. Examples of useful commercially available solid resins include C5 aliphatic hydrocarbon derived resins such as the ESCOREZ 1000 series from ExxonMobil Chemical Co., Irving, Texas, the WINGTACK series from Cray Valley, Exton, Pennsylvania, the PICCOTAC series from Eastman Chemical Co., Kingsport, Pennsylvania, and the QUINTONE series from Zeon Corp., Tokyo, Japan. Other potentially useful resins include cycloaliphatic C9 hydrocarbon resins such as the ARKON P series (fully hydrogenated) and ARKON M series (partially hydrogenated) from Arakawa Chemical Inc., Chicago, Illinois; cycloaliphatic C10 hydrocarbons such as the ESCOREZ 5000 series from ExxonMobil Chemical Company; hydrogenated pure monomer resins such as the REGALREZ series from Eastman Chemical Company; gum rosin esters such as the FORAL series and STAYBELITE A and E series from Pinova, Inc., Brunswick, Georgia; tall oil rosin esters such as the STAYBELITE 900 series from Kraton Polymers, LLC, Houston, Texas; LLC, Houston, Texas), the WESTREZ 5000 series from MeadWestvaco Corp., Richmond, Virginia, and the PERMALYN series from Eastman Chemical Company; polyterpenes, such as the PICCOLYTE A, F, C, and S series from Pinova Corporation; turpentine, such as SYLVARES TP 2019 from Kraton Polymers LLC.Examples of useful commercially available liquid resins include, but are not limited to, alpha-pinene derived polyterpenes such as those available from Pinova under the trade name PICCOLYTE A25; beta-pinene derived polyterpenes such as those available from Pinova under the trade name PICCOLYTE S25; hydrogenated C9 derived aliphatic resins such as those available from Eastman Chemical Company under the trade name REGALREZ 1018 and those available from Clay Valley under the trade name WINGTACK 10; and tall oil based liquid rosin esters such as those available from Kraton Polymers under the trade name SYLVALITE RE10L. Compatible tackifying resins may be a mixture of solid and liquid and should minimize interference with the electron beam curing step. The presence of aromatic content may reduce the efficiency of electron beam curing.
[0033] Radiation-crosslinkable pressure-sensitive adhesive precursor and adhesive preparation and articles containing the same
[0034] The radiation-crosslinkable pressure-sensitive adhesive precursors disclosed herein are easily prepared and processed by hot melt and solvent mixing and coating methods known to those of ordinary skill in the relevant art, and are described in International Publication WO 2016 / 106003 (D'Haese et al.). The radiation-crosslinkable pressure-sensitive adhesive precursor mixture can be exposed to electron beam ("EB") radiation to induce crosslinking of the radiation-crosslinkable pressure-sensitive adhesive precursor and provide an adhesive composition. EB doses suitable for embodiments of the present disclosure are typically 4 megarads ("MR") to 10MR. For example, for coating thicknesses ranging from 0.001" to 0.004" (0.00254cm to 0.01016cm), sufficient gel content and crosslinking are achieved at 6MR and 175 kilovolts ("kV") accelerating energy. The final composition preferably has a corrected gel content greater than 50%. This generally corresponds to sufficient crosslinking to provide clean removal (i.e., no oily residue) and no flow occurring (i.e., no G' / G" crossover temperature) at a frequency of 1 Hz over a temperature range from ambient temperature (e.g., 22°C) to above 150°C. G' is the storage modulus and G" is the loss modulus. At a frequency of 1 Hz and temperatures above 22°C, the corresponding tangent delta (δ) is in the range of 0.4 to 0.6 to provide a pressure sensitive adhesive that can be used for clean removal from stainless steel. Prior to EB crosslinking, the coating composition can be blended and / or foamed with a compatible polymer component.
[0035] The radiation cross-linked pressure-sensitive adhesive and radiation cross-linked pressure-sensitive adhesive precursor of the present disclosure, particularly hot melt and solution processable adhesive and precursor, can be advantageously used to prepare various adhesive tapes and articles. Many of these tapes and articles contain backing or other substrates to support the layer of adhesive. Other adhesive tapes and articles do not contain backing or substrate layers and are therefore self-supporting adhesive layers. Double-sided tapes are an example of such adhesive articles. Double-sided tapes are also called "transfer tapes", which are adhesive tapes with adhesive on both exposed surfaces. In some transfer tapes, the exposed surface is just the two surfaces of a single adhesive layer. Other transfer tapes are multilayer transfer tapes with at least two layers of adhesive layers that may be the same or different, and in some cases the middle layer of a non-adhesive layer. For example, the multilayer transfer tape can be a 3-layer structure with an adhesive layer, a film layer and another adhesive layer. The film layer can provide grip and / or tear strength or other desired characteristics. In the present disclosure, a double-sided adhesive comprising a self-supporting pressure-sensitive adhesive layer is prepared. Since the double-sided adhesive is self-supporting, it must have enough handling strength to operate in the absence of a support layer.
[0036] Adhesives of the present disclosure can be used to prepare medical products, including adhesives, such as, for example, surgical tapes and sterile drapes, bandages, sports tapes and wound dressings. Adhesives disclosed herein can be applied to any backing suitable for medical use using solvents or hot melt methods well known in the art, including, for example, occlusive (substantially airtight) and non-occlusive (air-permeable) backings. Occlusive backings are also referred to as low-porosity backings. Non-limiting examples of occlusive backings include films, foams and their laminates. Non-limiting examples of non-occlusive backings include woven substrates, non-woven substrates (such as spunlace materials or meltblown fiber webs), foams and heat-embossed non-woven substrates. Adhesives of the present invention are suitable for continuous (knife or contact rod), discontinuous (e.g., stripe coating) or pattern coatings, which can provide spatially different (e.g., points, triangles or squares) or spatially thick and thin adhesive regions on substrates.
[0037] Objects and advantages of this disclosure are further illustrated by the following non-limiting examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit this disclosure.
[0038] Example
[0039] Unless otherwise indicated or readily apparent from the context, all parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight. Unless otherwise indicated, the materials used in the examples were obtained from commercial suppliers (e.g., Aldrich Chemical Co., Milwaukee, Wisconsin.) and / or prepared by known methods. The following abbreviations are used in the examples: pphm = parts per hundred of acrylic acid monomer, EB = electron beam, rpm = revolutions per minute, in = inch, mil = thousandth of an inch, °F = degrees Fahrenheit, °C = degrees Celsius, min = minute, mW = milliwatt, cm 2 =square centimetre, oz = ounce, Hz = Hertz.
[0040] Materials used in the examples
[0041]
[0042]
[0043] Test Method
[0044] Gel content test method
[0045] Scrape the sample from the polyethylene terephthalate (PET) film after EB crosslinking. For each sample, weigh about 0.5 grams of adhesive component from each sample. This weight is referred to as the sampling weight in the formula below. The weighed sample is added to 50 grams of 50 / 50 toluene / ethyl acetate in a glass jar and placed on a mechanical roller at room temperature for 1 to 2 days. Filter the mixture with a 200 mesh screen. The screen and insoluble material are dried at 220°F (104°C) for 1 to 2 hours. Measure the weight of the insoluble component and refer to the insoluble weight in the formula below. Calculate the corrected gel content according to the following formula:
[0046]
[0047] where χ AEC is (sampling weight * preparation weight fraction),
[0048] The weight fraction of the prepared preparation = weight % of the preparation example / 100.
[0049] Test method for adhesion to stainless steel
[0050] The adhesion of samples coated on PET film and crosslinked by EB to stainless steel (ATSS) was tested under controlled temperature and humidity (CTH) conditions. ATSS was measured in a 180° peel geometry using a 12 inch / minute (ipm) (4.7 cm / min) rate. Within 5 minutes of bonding the tape to a clean steel plate, a 6 inch (3 cm) long and 1 inch (0.4 cm) wide strip was tested using a 3M90 Slip / Peel Tester obtained from Instrumentors, Inc. (Strongsville, OH) under the trade name T65871. The strip was bonded using 4 rolls of a 4.5 pound roller. The average time at 12 ipm was 2 seconds. The resulting peel force was recorded as ATSS, the cleanliness of the steel surface was evaluated, and recorded as the failure mode in Table 4.
[0051] Dynamic Mechanical Analysis (DMA) Test Method
[0052] The tests were conducted using an ARES-G2 rheometer from TA Instruments, New Castle, DE, with 8 mm disposable aluminum parallel plates attached to both the upper and lower fixtures. The "Low and High Temperature Ramp" test method was used to measure the temperature dependence of tangent δ (Tan δ) and loss / storage modulus (G' and G'', respectively) at a frequency of 1 Hz. After EB crosslinking, the sample was scraped from the PET film using a toothpick, pressed to 1 mm to 2 mm thick, and allowed to thermally relax. After holding at 30°C for 180 seconds, the first ramp of the DMA test was started at 30°C, and the temperature was decreased at a rate of 3°C / min until the defined Tan δ peak (glass transition temperature / Tg) was reached. The second ramp of the DMA test involved increasing the temperature from 30°C to 150°C at a rate of 3°C / min. The results from the two ramps were combined to determine the Tan δ value. Automatic strain adjustment was enabled to ensure that the material was in the linear viscoelastic region (LVR) during all temperature ramps.
[0053] Preparation Example (PE-1 and PE-2)
[0054] For each preparation example, an acrylate copolymer was prepared as follows: a monomer mixture was prepared by blending acrylic monomer, IOTG, photoinitiator and antioxidant A in a wide-mouth bottle in the amounts shown in Table 2. A magnetic stirring bar was placed in the mixture, and the mixture was placed on a stirring plate to form a curable composition. The EVA film was heat-sealed to form an open-ended container, each container measuring 18 cm×5 cm. Each container was filled with approximately 24 grams of curable composition. The air was exhausted from the opening and then sealed using a heat sealer (obtained from JJ Elemer Corp., St. Louis, MO, under the trade name “MIDWEST PACIFIC IMPULSE SEALER”). The sealed EVA film container encapsulated with the curable composition was immersed in a constant temperature water bath at 16°C and exposed to ultraviolet light (365nm, 4.5mW / cm 2 ) for nine minutes to polymerize the curable composition. As described below, the curable composition in its container was placed in the melt mixer used in Examples and Comparative Examples.
[0055] Table 2. Composition
[0056]
[0057] Examples (EX-1 to EX-6) and Comparative Examples (CE-1 and CE-2)
[0058] Each sample PE-1 or PE-2 as shown in Table 3 was mixed with antioxidant B and KAYDOL in the amounts shown in Table 3 using a melt mixer (twin screw extruder with a diameter of 30 mm). For each sample, 140 grams of the mixture was loaded into the mixer and mixed for 3 minutes at a screw speed of 150 rpm. The mixture was discharged by a heated gear pump operating at 200 rpm. As shown in Table 3, the samples were extruded using a contact die with a width of about 4 inches and 18 grains / 24 inches. 2 Coating weight (0.003 inches thick - 75 g / m 2 (GSM)) was coated onto a 1.2 mil thick PET film or crepe paper. The release coated PET liner was laminated onto the sample surface opposite the PET film or crepe paper. The sample was exposed to radiation from an electron beam source using a CB-300 electron beam generator (obtained from Energy Sciences, Inc., Wilmington, Mass., USA). The uncured material was exposed to EB irradiation through the release liner. The sample composition, EB dose after the release liner, and the coating weight are shown in Table 3. The characterization of the sample after EB irradiation is shown in Table 4.
[0059] Table 3. Compositions of Examples and Comparative Examples
[0060]
[0061] Table 4. Characterization of Examples and Comparative Examples
[0062]
[0063] NM = Not Measured
[0064] cln = clean removal, no residue observed on stainless steel after 180° peel
[0065] All references, patents and patent applications cited in the above patent applications are incorporated herein by reference in their entirety in a consistent manner. In the event of inconsistency or conflict between the incorporated references and the present application, the information in the foregoing description shall prevail. The foregoing description, which is given to enable a person of ordinary skill in the art to practice the present disclosure protected by the claims, should not be construed as limiting the scope of the present disclosure.
Claims
1. A radiation-crosslinkable pressure-sensitive adhesive precursor comprising: 40 to 90 weight percent of an acrylate copolymer, wherein the acrylate copolymer comprises C4 to C16 acrylic acid monomers; and 10% to 50% by weight of a hydrophobic oil.
2. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, comprising 40% to 80% by weight, optionally 50% to 90% by weight, or optionally 50% to 80% by weight of the acrylate copolymer.
3. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, wherein the C4 to C16 acrylic monomer comprises 10 to 100 wt%, optionally 20 to 80 wt%, optionally 30 to 70 wt% of C10 to C16 acrylic monomer. 4 . The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 3 , wherein the C10 to C16 acrylic monomer is selected from the group consisting of a primary acrylic monomer, a secondary acrylic monomer, and a combination thereof.
5. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 4, wherein the C10 to C16 acrylic monomer is selected from the group consisting of decyl acrylate, isononyl acrylate, 2-dodecyl acrylate, 2-propylheptyl acrylate, isodecyl acrylate, tridecyl acrylate, 2-decyl acrylate, 2-tetradecyl acrylate and combinations thereof.
6. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, wherein the C4 to C16 acrylic monomer comprises 10 to 100 wt%, optionally 20 to 80 wt%, optionally 30 to 50 wt% of C4 to C8 acrylic monomer.
7. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 6, wherein the C4 to C8 acrylic monomer is selected from the group consisting of butyl acrylate, hexyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, 2-octyl acrylate, isooctyl acrylate, and combinations thereof.
8. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, comprising 10 to 50 wt%, optionally 20 to 40 wt% of the hydrophobic oil.
9. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, wherein the hydrophobic oil is selected from the group consisting of paraffin oil, naphthenic oil, polypropylene glycol having a molecular weight in the range of 400 g / mol to 2000 g / mol, polybutene having a molecular weight in the range of 350 g / mol to 1500 g / mol, and combinations thereof.
10. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, further comprising 0.01 to 5 wt%, optionally 0.01 to 4 wt%, optionally 0.01 to 2 wt% of a polar acrylic monomer. 11 . The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 10 , wherein the polar acrylic monomer is selected from the group consisting of acrylic acid, N,N-dimethylacrylamide, and combinations thereof.
12. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, further comprising 0.1 wt% to 10 wt%, optionally 0.1 wt% to 5 wt%, optionally 2 wt% to 5 wt% of a high Tg acrylate monomer.
13. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, wherein the high T g The acrylate monomer is selected from the group consisting of isobornyl acrylate, polystyrene macromonomers, and combinations thereof.
14. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, further comprising an additive selected from the group consisting of a photoinitiator, a chain transfer agent, an antioxidant, a tackifying resin, and combinations thereof.
15. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, having a weight average molecular weight Mw of 500,000 to 1,500,000 g / mol, optionally 750,000 to 1,000,000 g / mol, as determined by gel permeation chromatography.
16. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, wherein the acrylate copolymer is free of insoluble gel as determined by the Calibrated Gel Test.
17. The radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1, wherein the acrylate copolymer does not contain multifunctional acrylate.
18. An adhesive comprising the radiation-crosslinkable pressure-sensitive adhesive precursor according to claim 1 in crosslinked form.
19. The adhesive of claim 18, wherein the crosslinked form of the radiation-crosslinkable pressure-sensitive adhesive precursor is formed by exposing the radiation-crosslinkable pressure-sensitive adhesive precursor to electron beam radiation.
20. The adhesive of claim 18, wherein the adhesive has a corrected gel content of 50 wt% to 90 wt%, optionally 50 wt% to 80 wt%, optionally 50 wt% to 70 wt%.
21. An article comprising the precursor according to claim 1.
22. An article comprising the adhesive of claim 18.
